Micromonas micros Infection of a Prosthetic Hip Joint: A Case Report and Review of the Literature - Abhimanyu Aggarwal; Durane Walker (Case Reports in Infectious Diseases)
Micromonas micros is an oral anaerobic Gram-positive coccus and is a commensal of the mouth, and it is rarely isolated in prosthetic joint infections (PJIs) and even less frequently related to a preceding dental procedure with eventual hematogenous seeding of the prosthetic joint. Here, we present a case of a 56-year-old male with a prosthetic hip joint who developed Micromonas micros prosthetic hip joint infection with symptoms starting a few days after a dental procedure and not having received periprocedural antibiotic prophylaxis. He recovered well with surgical intervention and antimicrobial therapy. We conducted a literature review of prosthetic hip joint infections caused by Micromonas micros as well as briefly discuss current guidelines on antibiotic prophylaxis in patients with prosthetic joints undergoing dental procedures and some knowledge gaps.